Progress in Synthesis of Monoglycerides for Use in Food and Pharmaceuticals - Rarokar, Nilesh Ramesh; Menghani, Sunil; Kerzare, Deweshri; Khedekar, Pramod Bhujangrao (Fakultas Farmasi, Universitas Gadjah Mada, 2017)
Glycerides are lipid esters of the glycerol molecule and fatty acids. Their primary function is the storage of energy. Due to its structure and properties, glycerol participates in the formulation or synthesis of many compounds such as food products, cosmetics, pharmaceuticals, liquid detergents. Monoglycerides (MGs) can be formed by both industrial chemical glycerolysis and biological or enzymatic processes. Chemical glycerolysis bring issues of low MGs yield, high operating temperature, formation of undesirable by-products and high energy consumption. On the other hand enzymatic processes have advantages of mild reaction conditions and high purity of MGs. But, several purification steps are required to obtain food or pharmaceutical grade MG, such as neutralization of the reaction media and discoloration followed by expensive molecular distillation. The purpose of this article is to review the main challenges in the synthesis of MGs from triglycerides (TGs) contained in the various fixed oils and application thereof in the food and pharmaceuticals.Â Keywords: Â Catalyzation, glycerolysis, molecular distillation, monoglycerides, solid catalysts.